1998
DOI: 10.1111/j.1749-6632.1998.tb10684.x
|View full text |Cite
|
Sign up to set email alerts
|

Galanin Causes Cl Secretion in the Human Colon: Potential Significance of Inflammation‐Associated NF‐κB Activation on Galanin‐1 Receptor Expression and Function

Abstract: Galanin is widely distributed in enteric nerves and nerve terminals throughout the gastrointestinal (GI) tract. Within the GI tract galanin is best known for its ability to alter smooth muscle contractility and regulate intestinal motility. However, recent studies also indicate that galanin can modulate epithelial ion transport. We previously showed that epithelial cells lining the human GI tract, including those of colonic origin, express Gal1 galanin receptors (Gal1-R). We herein demonstrate that epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 45 publications
1
34
1
Order By: Relevance
“…76 Indeed, inflammation up-regulates this receptor by an NF-B-dependent pathway. 77 Interestingly, pathogenic E. coli, but not the nonpathogenic strain, activate NF-B, and increase Gal-R1 mRNA synthesis. 78 …”
Section: Galanin R1mentioning
confidence: 99%
“…76 Indeed, inflammation up-regulates this receptor by an NF-B-dependent pathway. 77 Interestingly, pathogenic E. coli, but not the nonpathogenic strain, activate NF-B, and increase Gal-R1 mRNA synthesis. 78 …”
Section: Galanin R1mentioning
confidence: 99%
“…Galanin belongs to the group of substances regulating the contractility of intestines, may modulate the transepithelial ion transport and the intestinal epithelial cells express Gal1 receptors (Benya et al, 1998). In the same paper, it was found that the expression of this receptor increases in the human colon undergoing inflammatory changes.…”
Section: Resultsmentioning
confidence: 96%
“…Studies conducted on humans with IBD show an increase in GAL1R receptor expression in the colon of UC and CD patients (Benya et al 1998).…”
Section: Galanin (Gal)mentioning
confidence: 99%